Gall wasps and their parasitoids in cork oak fragmented forests - CHUST, GUILLEM; GARBIN, LUCAS; PUJADE-VILLAR, JULI (Ecological Entomology, 2007)
Abstract 1. This paper explores the potential effects of host-plant fragmentation on cork oak gall wasp populations (Cynipidae, Hymenoptera) and on their predators, lethal inquilines, and parasitoids. To address this objective, galls were collected across a gradient of cork oak (Quercus suber) forest fragmentation in the East Pyrenees (Albera, Spain), and they were incubated to obtain the parasitism rates. 2. Two hypotheses were tested: (1) Host-plant fragmentation may induce a decline in gall wasp populations because of area and isolation effects on local extinction and dispersal; as a consequence of that, parasitoids may decline even more strongly in fragmented habitats than their prey. (2) Host-plant fragmentation may cause a decline in gall wasp parasitoid populations that, in turn, can lead to an ecological release in their prey populations. 3. Among the eight cork oak gall wasps sampled in the study area of Albera, the gall abundances of three species (Callirhytis glandium, Callirhytis rufescens, and Andricus hispanicus) were significantly related to forest fragmentation. The overall abundance of gall wasps was affected by a radius of ≈ 890 m surrounding landscape, presenting constant abundances with forest loss until forest cover is reduced at ≈ 40%; below that value the abundance increased rapidly. Three inquilines and 23 parasitoids species were recorded after gall incubation. In 25 cases, species of inquilines and parasitoids were newly recorded for the corresponding host in the Iberian peninsula. 4. Although the overall parasitism rate was high (1.1), it was uncorrelated with fragmentation and with overall cynipid abundance. These results indicate that host-plant fragmentation was correlated with higher abundance of gall wasps, whereas the parasitism rate could not explain this hyper-abundance in small forest fragments.
Keywords: Cork oak; fragmentation; gall wasp; parasitism rate; parasitoid; Pyrenees; Quercus suber

Gall wasps and their parasitoids in cork oak fragmented forests - CHUST, GUILLEM; GARBIN, LUCAS; PUJADE-VILLAR, JULI (Ecological Entomology, 2007)
Abstract 1. This paper explores the potential effects of host-plant fragmentation on cork oak gall wasp populations (Cynipidae, Hymenoptera) and on their predators, lethal inquilines, and parasitoids. To address this objective, galls were collected across a gradient of cork oak (Quercus suber) forest fragmentation in the East Pyrenees (Albera, Spain), and they were incubated to obtain the parasitism rates. 2. Two hypotheses were tested: (1) Host-plant fragmentation may induce a decline in gall wasp populations because of area and isolation effects on local extinction and dispersal; as a consequence of that, parasitoids may decline even more strongly in fragmented habitats than their prey. (2) Host-plant fragmentation may cause a decline in gall wasp parasitoid populations that, in turn, can lead to an ecological release in their prey populations. 3. Among the eight cork oak gall wasps sampled in the study area of Albera, the gall abundances of three species (Callirhytis glandium, Callirhytis rufescens, and Andricus hispanicus) were significantly related to forest fragmentation. The overall abundance of gall wasps was affected by a radius of ≈ 890 m surrounding landscape, presenting constant abundances with forest loss until forest cover is reduced at ≈ 40%; below that value the abundance increased rapidly. Three inquilines and 23 parasitoids species were recorded after gall incubation. In 25 cases, species of inquilines and parasitoids were newly recorded for the corresponding host in the Iberian peninsula. 4. Although the overall parasitism rate was high (1.1), it was uncorrelated with fragmentation and with overall cynipid abundance. These results indicate that host-plant fragmentation was correlated with higher abundance of gall wasps, whereas the parasitism rate could not explain this hyper-abundance in small forest fragments.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cork oak; fragmentation; gall wasp; parasitism rate; parasitoid; Pyrenees; Quercus suber

Histological modifications on Quercus suber twigs (Fagaceae) caused by the gallwasp Plagiotrochus suberi (Hymenoptera: Cynipidae). - Garbin, L.; Durfort, M.; Diaz, N. B.; Pujade-Villar, J. (Entomologia generalis., 2005)
Intact healthy twigs of Quercus suber were compared anatomically with twigs containing larval chambers of the gall wasp species Plagiotrochus suberi Weld 1926 using different staining techniques. A reorganisation of the tissues close to the larval chamber was found.The most important histological modifications in this zone are the presence of abnormal vessels, a higher frequency of tannin cell bundles, a higher number of cells with lipid inclusions,a highly disorganized cellular structure of the epidermis and subepidermal cortical tissues and the presence of pluriestratified epidermal invaginations. All these peculiarities are commented,compared and discussed
Keywords: gall wasp; histological modification; larval chamber; phytopathology; Plagotrochus suberi Weld 1926; plant anatomy

Histological modifications on Quercus suber twigs (Fagaceae) caused by the gallwasp Plagiotrochus suberi (Hymenoptera: Cynipidae). - Garbin, L; Durfort, M; Diaz, N B; Pujade-Villar, J (Entomologia generalis., 2005)
Intact healthy twigs of Quercus suber were compared anatomically with twigs containing larval chambers of the gall wasp species Plagiotrochus suberi Weld 1926 using different staining techniques. A reorganisation of the tissues close to the larval chamber was found.The most important histological modifications in this zone are the presence of abnormal vessels, a higher frequency of tannin cell bundles, a higher number of cells with lipid inclusions,a highly disorganized cellular structure of the epidermis and subepidermal cortical tissues and the presence of pluriestratified epidermal invaginations. All these peculiarities are commented,compared and discussed
Keywords: gall wasp; histological modification; larval chamber; phytopathology; Plagotrochus suberi Weld 1926; plant anatomy